Endocrinological disorders in children with cutis-laxa syndromes - Mirela Elena Iancu; Alice Ioana Albu; Raluca Maria Vlad; Dragos Nicolae Albu (Amaltea Medical Publishing House, 2022)
Cutis laxa syndromes is a rare, multisystem disorder, which primary involves the skin, caused by various mutations in genes that code structural or functional components of the elastic fiber, resulting in heterogenous manifestations. Diagnosis is primarily based on the physical examination, but supported by molecular tests, and guides treatment and monitoring of the patients. Endocrinological complications are sparsely described, with short stature, osteoporosis and fractures being the most frequent. The precise mechanisms are not elucidated and reports about condition-specific treatments are rare. This review provides an overview of the endocrinological disturbances reported in association with cutis laxa syndromes.